Marvel-verse. She-Hulk. - Lee, Stan, 1922-2018 (Marvel Worldwide, Inc, 2021)
Contains a collection of five graphic novel short stories about the adventures of She-Hulk. First, Bruce Banner's cousin Jennifer Walters is transformed into the She-Hulk after she is shot and Bruce is forced to give her a lifesaving blood transfusion. Next, the She-Hulk meets the Blonde Phantom and learns about the precarious nature of life as a superhero. Then, the Enchantress brings together She-Hulk, Hellcat, Marvel Girl, and the Scarlet Witch for her evil plan to take down Thor, and Mary Jane must come up with a plan to help them defeat her. Later, She-Hulk and Spider-Man team up to save the city from an ancient Egyptian threat. Finally, a bounty hunter mistakes She-Hulk for Gamora, and the two join forces to fight him off.